2013
DOI: 10.1053/j.gastro.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein Up-regulates Jagged-1 and Activates the NOTCH Pathway in Human Hepatocellular Carcinoma

Abstract: Background & Aims Cancer cells often lose contact inhibition to undergo anchorage-independent proliferation and become resistant to apoptosis by inactivating the Hippo signaling pathway, resulting in activation of the transcriptional co-activator yes-associated protein (YAP). However, the oncogenic mechanisms of YAP are unclear. Methods Using cross-species analysis of expression data, the Notch ligand Jagged-1 (Jag-1) was identified as downstream target of YAP in hepatocytes and hepatocellular carcinoma (HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
244
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(266 citation statements)
references
References 43 publications
10
244
1
2
Order By: Relevance
“…These data indicate that MOB1A/1B maintain oval cell quiescence and function as potent tumor suppressors in the liver. The liver phenotypes of LMob1DKO mice are more dramatic than those of mice with liver-specific mutations of Nf2 (14) effects than TEAD2/3 on transcriptional targets in human liver cells (12). Finally, we have demonstrated that TAZ and TGF-β2/3 are also critical Hippo signaling effectors whose loss mitigates the liver phenotypes of LMob1DKO mice.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These data indicate that MOB1A/1B maintain oval cell quiescence and function as potent tumor suppressors in the liver. The liver phenotypes of LMob1DKO mice are more dramatic than those of mice with liver-specific mutations of Nf2 (14) effects than TEAD2/3 on transcriptional targets in human liver cells (12). Finally, we have demonstrated that TAZ and TGF-β2/3 are also critical Hippo signaling effectors whose loss mitigates the liver phenotypes of LMob1DKO mice.…”
Section: Discussionmentioning
confidence: 73%
“…preventing it from activating TEA domain family member (TEAD)-mediated transcription of connective tissue growth factor (CTGF) (9), secreted phosphoprotein 1 (SPP1) (10), transforming growth factor beta (TGFβ) (11), and Jagged 1 (JAG1) (12). Phosphorylated YAP1/TAZ also binds to E3-ubiquitin ligase SCF βTRCP and is degraded (13).…”
Section: Significancementioning
confidence: 99%
“…Cells were treated by PD98059 (15-50 lM, Cell Signaling Technology (CST), Boston, MA, USA) or U0126 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) lM, CST) 24 h before harvest. ShRNAs were cloned into pLKO.1 lentiviral vectors using primers as follows: MEK1-sh#1-Forward: CCGGAACTCTGGATCAAGTCCTGAACTCGAGTTCAGGACTTGATCCA-GAGTTTTTTTG and Reward: AATTCAAAAAAACTCTGGATCAAGTC C TGAACTCGAGTTCAGGACTTGATCCAGAGTT; MEK1-sh#2-Forward: CCGGAAGGACTCATTACTCTGTGCACTCGAGTGCACAGAGTAATGAGT CCTTTTTTTG and Reward: AATTCAAAAAAAGGACTCATTACTCTG TGCACTCGAGTGCACAGAGTAATGAGTCCTT.…”
Section: Cell Culture and Vectorsmentioning
confidence: 99%
“…By using cross-species analysis of expression data, the Notch ligand Jagged-1 (Jag-1) was identified as a downstream target of YAP in HCC cells. Overexpression of YAP upregulates Jag-1, leading to activation of Notch pathway and increased proliferation [6]. Having an essential role in cellular growth, knockout of the YAP gene in mice could lead to early embryonic lethality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Les mécanismes par lesquels YAP exerce ces propriétés oncogéniques dans le foie ne sont pas encore parfaitement compris. Une hypothèse récente suggère que YAP augmenterait l'expression de Jag-1, activant la voie Notch dans les hépatocytes et les lignées tumorales de CHC, mais de façon indépendante de la β-caténine [25]. Un mécanisme similaire est également décrit dans l'intestin, puisqu'un inhibiteur de Notch restreint la dysplasie intestinale induite par YAP [18].…”
Section: Hippo Et Wnt En Cancérologie Digestiveunclassified